2011
DOI: 10.1152/ajplung.00123.2011
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin signaling is required for TGF-β1-induced extracellular matrix production by airway smooth muscle cells

Abstract: Chronic inflammatory airway diseases like asthma and chronic obstructive pulmonary disease (COPD) are characterized by airway remodeling with altered extracellular matrix (ECM) deposition. Transforming growth factor-β1 (TGF-β1) is upregulated in asthma and COPD and contributes to tissue remodeling in the airways by driving ECM production by structural cells, including airway smooth muscle. In this study, we investigated the activation of β-catenin signaling and its contribution to ECM production by airway smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 63 publications
(103 reference statements)
4
49
1
2
Order By: Relevance
“…We furthermore showed that TGFb-induced fibronectin and a-sm-actin expression was dependent on b-catenin (10,11). This underscores the role of WNT signaling in fibroblast activation and remodeling as well as the cross-talk that exists between TGF-b and WNT signaling in these responses.…”
Section: Wnt Signalingsupporting
confidence: 52%
See 1 more Smart Citation
“…We furthermore showed that TGFb-induced fibronectin and a-sm-actin expression was dependent on b-catenin (10,11). This underscores the role of WNT signaling in fibroblast activation and remodeling as well as the cross-talk that exists between TGF-b and WNT signaling in these responses.…”
Section: Wnt Signalingsupporting
confidence: 52%
“…Recent findings indicate similar key roles for the Wingless/integrase-1 (WNT) signaling pathway in tissue homeostasis and remodeling in many organ systems, including the lung (8)(9)(10)(11)(12). WNT ligands bind to transmembrane Frizzled (FZD) receptors and can thereby control cell differentiation, growth, and polarity in a variety of cell systems.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…4) (9,79,121,163,201,216,217,347). For example, expression of contractile proteins is enhanced in human ASM cells exposed to both methacholine and TGF-␤ (216,217).…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…Transforming growth factor (TGF)-β1 stimulates ECM synthesis in cultured cells, including renal, vascular smooth muscle and type-II pulmonary epithelial cells (20)(21)(22). TGF-β1 is also involved in MSC proliferation (23).…”
Section: Introductionmentioning
confidence: 99%